ความสัมพันธ์ระหว่างปัจจัยส่วนบุคคล การสนับสนุนทางสังคมและความผาสุกทางจิตวิญณาณกับเชาวน์อารมณ์ของนักศึกษาพยาบาล วิทยาลัยพยาบาล สังกัดกระทรวงสาธารณสุข - ลักขณา แพทยานันท์ (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
The purposes of this research were to study factors associated with and probably could predict emotional quotient of nursing students. These variables include personal factors, social support and spiritual well-being. The samples consisted of 428 nursing students in nursing colleges under the jurisdiction of the Ministry of Public Health. Selected by multi-stage sampling technique. The research instruments developed by the investigator, were questionnaires regarding social support, spiritual well-being and Bar-On Emotional Quotient Inventory (Bar-On EQ-i). The questionnaires were tested for validity by panel experts. Alpha Cronbach reliability coefficients were .94, .92 and .91 respectively. The data were analyzed by using Pearson s product moment correlation and stepwise multiple regression analysis. The major findings were as follow: 1. Emotional Quotient of nursing students in all aspects were at average level (X = 3.47) from EQ-i standard score 57.45-139.34. 2. Spiritual well-being, social support and level of class for bachelor s degree were positive correlated with emotional quotient of nursing students at the .05 level. 3. Spiritual well-being and social support were the factors that significantly predicted emotional quotient of nursing students at the level of .05. These predictors accounted for 21.81 percent (R2 = .2181) of the variance. The standardized equation derived from the analysis was: emotional quotient = .3560 spiritual well-being + .2340 social support.